PEMBERIAN PUPUK VERMIKOMPOS PADA BIBIT KOPI ROBUSTA (Coffea canephora Pierre) - Pertiwi, Irfani; ', Ardian (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The research aim to knows impact of giving Vermicompost fertilizer to breeding coffee Robusta (Coffea canephora Pierre) and gets the best recommanded to doses. Research conducted in UPT area of research farm in faculty of agriculture, Riau University on Bina Widya Campus Km 12,5 sub-district of Simpang Baru, district of Tampan, Pekanbaru during 3 months from April 2015 until July 2015. This research arranged experimentally by using Completely Randomized Design which consist of 5 treatments where it repeated as much as 4 times and then obtained 20 experimental units with 3 sample each unit. Parameter observed plant height increment, number of leaves increment, increase the girth and leaf area. Data were analyzed statistically using analysis of variance (ANOVA) and followed by LSD at level of 5%. The result showed that giving vermicompost fertilizer with 75 g/10 kg soil can give the best result to plant height increment, number of leaves increment, increase the girth and leaf area. Keywords : Vermicompost fertilizer, breeding, Coffee Robusta.